Pengaruh Inflasi, Indeks Pembangunan Manusia, dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi Kota Palopo - Hikmad H; I Ketut Patra; Sri Wahyuny Mustafa (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The purpose of this study is to analyze how inflation, the Human Development Index (HDI), and government spending affect economic growth in Palopo City. This study employs a quantitative descriptive methodology and uses secondary data from the period 2014–2023, obtained from the Palopo City Central Statistics Agency (BPS) Year-End Report publications. The sample period for this study covers 10 years. Economic growth serves as the dependent variable, while inflation, the HDI, and government spending are the independent variables. Data analysis was conducted using IBM SPSS 25 software and multiple regression methods. Classical assumption tests—including normality, multicollinearity, heteroscedasticity, and autocorrelation—were performed. The results show that inflation has no significant effect on economic growth. The HDI has a positive and significant effect, while government spending has a positive but insignificant effect. The adjusted R² value of 0.893 indicates that these three variables explain a large proportion of the variation in economic growth. This study highlights that improving the quality of human resources—through purchasing power, health, and education—has a greater impact on economic growth in Palopo City than either increasing government spending or controlling inflation. The findings provide theoretical support for endogenous growth theory, which emphasizes human resources as a key factor in long-term economic growth. To promote sustainable and equitable development, this study recommends that local governments prioritize policies aimed at improving the quality of human resources and ensure the effective and transparent allocation of public funds.